Analyzing Textuality in the Students English Written Text - Yohannes Telaumbanua (Scopus ID: 57214719658 ); Muthia Damaiyanti (Politeknik Negeri Padang, 2015)
This research aims at observing and investigating the Seven Standards of Textuality in the Students’ English Written Texts. The methodology used was qualitative case study research. The setting was at Islamic Senior High School Students (MAN) Lembah Melintang whereas; the research participants were Islamic Senior High School “Excel” Students. The number of the research participants was 35. The research finding indicates that the students were frequent to produce the textuality errors in their English written texts. The number of errors of cohesion (substitution: 60, ellipsis: 28, reference: 50, conjunction: 78 and lexical cohesion: 156 times) was 372 times, of coherence (additional ideas: 34, contrary: 21, and summary: 35 times, whereas; the cause-effect relationship and example/specific meaning were not found or produced) was 90 times. The textuality error were mainly caused by interference or language transfer and interlanguage. In conclusion, the students have not been able to produce cohesion and coherence to achieve well-organized ideas in their English written texts. Meanwhile the other five standards of textuality were fair to concern and reasonably related. Interference or language transfer and interlanguage were the root of the problem in achieving well-established text’s standards of textuality